Delirium in the elderly: a clinical review. Issue 1006 (23rd July 2009) - Saxena, S; Lawley, D
Abstract : Delirium is a common condition in the elderly, affecting up to 30% of all older patients admitted to hospital. There is a particularly high risk of delirium in surgical inpatients, especially following operations for hip fracture or vascular surgery, but also for patients in the intensive care unit. Patients with delirium have higher morbidity and mortality rates, higher re-admission rates, and a greater risk of long term institutionalisation care, thereby having a significant impact on both health and social care expenditure. Delirium frequently goes unrecognised by clinicians and is often inadequately managed. Recent evidence suggests that a better understanding and knowledge of delirium among health care professionals can lead to early detection, the reduction of modifiable risk factors, and better management of the condition in the acute phase. Many cases of delirium are potentially preventable, and primary and secondary care services should be taking active steps in order to do prevent this condition.